Antibacterial and osteo-stimulatory effects of a borate-based glass series doped with strontium ions. (November 2016) - Li, Yiming; Stone, Wendy; Schemitsch, Emil H; Zalzal, Paul; Papini, Marcello; Waldman, Stephen D; Towler, Mark R
This work considered the effect of both increasing additions of Strontium (Sr 2+ ) and incubation time on solubility and both antibacterial and osteo-stimulatory effects of a series of glasses based on the B2 O3 –P2 O5 –CaCO3 –Na2 CO3 –TiO2 –SrCO3 series. The amorphous nature of all the glasses was confirmed by X-ray diffraction. Discs of each glass were immersed in de-ionized water for 1, 7 and 30 days, and the water extracts were used for ion release profiles, pH measurements and cytotoxicity testing. Atomic absorption spectroscopy was employed to detect the release of Na +, Ca 2+ and Sr 2+ ions from the glasses with respect to maturation, which indicated that the addition of Sr 2+ retarded solubility of the glass series. This effect was also confirmed by weight loss analysis through comparing the initial weight of glass discs before and after periods of incubation. The incorporation of Sr 2+ in the glasses did not influence the pH of the water extracts when the glasses were stored for up to 30 days. Cytotoxicity testing with an osteoblastic cell line (MC3T3-E1) indicated that glasses with the higher (20 mol% and 25 mol%) Sr 2+ incorporation promoted proliferation of osteoblast cells, while the glasses with lower Sr 2+ contents inhibited cell growth. The glass series, except for Ly-B5 (which contained the highest Sr 2+ incorporation; 25 mol%), were bacteriostatic against S. aureus in the short term (1–7 days) as a result of the dissolution products released.